Hormonal crosstalk for root development: a combined experimental and modeling perspective - Lindsey, Keith; Rowe, James; Liu, Junli (Frontiers in Plant Science, 2014)
Plants are sessile organisms and therefore they must adapt their growth and architecture to a changing environment. Understanding how hormones and genes interact to coordinate plant growth in a changing environment is a major challenge in developmental biology. Although a localized auxin concentration maximum in the root tip is important for root development, auxin concentration cannot change independently of multiple interacting hormones and genes. In this review, we discuss the experimental evidence showing that the POLARIS peptide of Arabidopsis plays an important role in hormonal crosstalk and root growth, and review the crosstalk between auxin and other hormones for root growth with and without osmotic stress. Moreover, we discuss that experimental evidence showing that, in root development, hormones and the associated regulatory and target genes form a network, in which relevant genes regulate hormone activities and hormones regulate gene expression. We further discuss how it is increasingly evident that mathematical modelling is a valuable tool for studying hormonal crosstalk. Therefore, a combined experimental and modelling study on hormonal crosstalk is important for elucidating the complexity of root development.